Improving survival and local control in rectal cancer in Catalonia (Spain) in the context of centralisation: A full cycle audit assessment. Issue 12 (December 2016) - Manchon-Walsh, P.; Aliste, L.; Espinàs, J.A.; Prades, J.; Guarga, A.; Balart, J.; Biondo, S.; Castells, A.; Sanjuan, X.; Tabernero, J.; Borras, J.M.; ,
Abstract: Background: Rectal cancer surgery in Catalonia has been involved in a process of centralisation. We assessed the impact of this health policy strategy on quality of care and clinical results. Methods: We compared patterns of care and clinical outcomes of all rectal cancer patients receiving radical surgery for the first time in public hospitals in two time periods, before (2005 and 2007) and after (2011–2012) centralisation, analysing indicators of care quality according to the regional clinical practice guidelines. Clinical outcomes at two years were also assessed. Results: A total of 3780 patients were included. From 2005 to 2012, the proportion of patients treated surgically for the first time in centres whose annual surgical caseload was more than 11 increased from 84.0% to 90.4%. The rate of locoregional recurrence at two years fell from 4.5 to 3.06/100 person-years (p = 0.005). The crude mortality rate at three months, one and two years was reduced by 55%, 40% and 34% (p < 0.001). Conclusion: Improvements in quality of care might be associated with the centralisation of surgery and with the selective focus effect derived from the process of auditing. Our results support the continuation of clinical auditing and surveillance of authorised centres.